2017
DOI: 10.1016/j.stem.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC Glial Mouse Chimeras Reveal Glial Contributions to Schizophrenia

Abstract: In this study, we investigated whether intrinsic glial dysfunction contributes to the pathogenesis of schizophrenia (SCZ). Our approach was to establish humanized glial chimeric mice using glial progenitor cells (GPCs) produced from induced pluripotent stem cells derived from patients with childhood-onset SCZ. After neonatal implantation into myelin-deficient shiverer mice, SCZ GPCs showed premature migration into the cortex, leading to reduced white matter expansion and hypomyelination relative to controls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
216
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(229 citation statements)
references
References 93 publications
12
216
0
1
Order By: Relevance
“…Dispersion of the grafted cells extended both rostrally and caudally of the injection site (Figure d). This distribution is in line with previous reports regarding human OPC transplantation into perinatal shiverer mice, which showed selective integration and dispersion of the grafted cells in the host white matter tract (Douvaras et al, ; Hu et al, ; Wang et al, ; Windrem et al, ). To determine the maturation of the grafted cells, we used GSTπ, an established marker for mature OL (Tamura et al, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Dispersion of the grafted cells extended both rostrally and caudally of the injection site (Figure d). This distribution is in line with previous reports regarding human OPC transplantation into perinatal shiverer mice, which showed selective integration and dispersion of the grafted cells in the host white matter tract (Douvaras et al, ; Hu et al, ; Wang et al, ; Windrem et al, ). To determine the maturation of the grafted cells, we used GSTπ, an established marker for mature OL (Tamura et al, ).…”
Section: Resultssupporting
confidence: 92%
“…Human pluripotent stem cells (hPSCs) can serve as an unlimited and scalable source of OPCs for cell therapy. Moreover, the discovery of induced pluripotent stem cells (iPSCs) has enabled a new era of patient‐specific disease modeling and drug screening (Douvaras et al, ; Goldman & Kuypers, ; Madhavan et al, ; Windrem et al, ). Over decades, numerous advances have improved the generation of OPCs from hPSCs (Douvaras, ; Hu, Du, Li, Ayala, & Zhang, ; Rodrigues et al, ; Stacpoole et al, ; Wang et al, ) and a related clinical trial for spinal cord injury (SCI) has been initiated (Lebkowski, ; Priest, Manley, Denham, Wirth, & Lebkowski, ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, a recent study found that glial progenitor cells from schizophrenic patients express significantly lower levels of NL1, NL2, and NL3 compared to controls. When these human glial progenitors were injected into mice, they caused neuronal dysfunction, perturbed animal behavior and yielded abnormal astrocytic morphologies 39 . In conclusion, our findings reveal how imperative it is to understand the full extent of NL functions in all cell types of the brain to completely comprehend the pathophysiology of these disorders.…”
Section: Astrocytic Nl2 Controls Synapse Functionmentioning
confidence: 99%
“…The engraftment of human glia in the mouse brain enhanced synaptic plasticity and learning in the transplanted mice (Han et al, 2013). Transplanting glial precursor cells derived from schizophrenia patients induced schizophrenia-like behaviors like excessive anxiety, antisocial traits and disrupted sleep in mice indicating a causal role of glial pathology in disease development (Windrem et al, 2017). …”
Section: Hpsc Models Of Complex Phenotypes - Interspecies Chimerasmentioning
confidence: 99%